Determination of Neonatal Prognosis Based on Umbilical Vein Blood Gas in Hakim Hospital of Neyshabur, Iran during 2017-2018 - Ghazaleh Doostparast Torshizi; Mahboobe Gholami; Bita Mohamadi; Ameneh Dehnavi (Mashhad University of Medical Sciences, 2020)
Background: In order to determine the prognosis of neonates, it is recommended to use umbilical gas analysis in all high-risk pregnancies. However, utilizing umbilical gas analysis and Apgar score together is very helpful for determining the mortality rate confidence interval. Therefore, in this study, we investigated the application of umbilical gas analysis in assessing the prognosis of infants. Methods: This cross-sectional study was conducted in Hakim Hospital of Neyshabur, Iran during 2017-2018 with 100 subjects in each group of control and test. Blood samples were collected from the umbilical vein of all neonates. The data were compared between the two groups by the t-test and Mann-Whitney test using the SPSS software version 18 at the significance level of P ≤ 0.05. Results: Our findings demonstrated that both hospitalization and the need for resuscitation had significant relationships with pH and base excess (BE) in the case and control groups (P<0.05). Moreover, 52.7% of the subjects in the intervention group and 47.3% of the participants in the control group were born through cesarean section. Therefore, the two groups were not significantly different regarding the route of delivery (P>0.05) Conclusion: According to the results of this study, a positive relationship was found between the neonatal prognosis and umbilical vein blood gas. Consequently, we can determine neonatal prognosis based on umbilical vein blood gas.